Analyzing the blood bank service quality from Indian blood donors' perspective: An empirical evidence - Shantanu Saha; Jayatee Bhattacharya (Wolters Kluwer Medknow Publications, 2019)
Objective: The objective of this study is to assess the levels of service quality provided by blood banks from blood donors' perspective and simultaneously judge the opinion of their satisfaction level based on SERVQUAL (service quality) variables, namely Reliability, Assurance, Tangibility, Empathy, and Responsiveness. Materials and Methods: A self-administered and respecified structured SERVQUAL questionnaire is prepared to address expectation and perception of services experienced by blood donors. A total of 280 blood donors' responses were collected by visiting blood banks. Results: The study endorsed all the significant five dimensions affecting the blood donors' expectation with actual service experienced during the exercise of donation. Average of overall service quality index gap is 0.38. Highest gap scores were significantly perceived in "Assurance" (Gap score 0.55) and "Empathy" (Gap score 0.49). In addition, "Tangibles," "Reliability," and "Responsiveness" scores are equitable, implying the blood donors' satisfaction level with the blood bank services. Conclusions: This study divulges blood bank's need to dissect and evaluate the level of service quality provided by them, along with consideration to the measurements of service quality gap models for the better fulfillment of blood contributors and retention.